Xanthine Oxidase and Adenosine Deaminase Activities of Renal Tissue in Rats with Hypertension Induced by N Sup Omega Nitro-L-Arginine Methyl Ester+ (Annals of Medical Research, 2021)
None
Keywords: Kidney, Hypertension, L-NAME, Xanthine oxidase, Adenosine deaminase